MOBILITAS PENDUDUK ANTARDAERAH DALAM RANGKA TERTIB PENGENDALIAN MIGRASI MASUK KE DKI JAKARTA - Haning Romdiati; Mita Noveria (Research Centre for Population, Indonesian Institute of Sciences, 2006)
This paper describes three interrelated aspects of migration phenomena to DKI Jakarta: permanent migration, temporary migration, and the efforts to manage the migrants in DKI Jakarta Province. Using the 1990 and the 2000 Indonesian Population Censuses, the data show that DKI Jakarta was the main destination of migrants from other provinces oflndonesia. The large job opportunities and various socio-economic infrastructures were likely to be the pull factors of migration to this city. The stream of migration into DKI Jakarta was characterized by two patterns; permanent and temporary, but the second pattern tends to be more significant recently. Temporary migrants who are generally characterized by un-skilled labors, generally are working in informal sector and living in slums areas. Most of these migrants tend to ignore population administration: they do not have temporary ID cards as regulated by the government of DKI Jakarta. These problems should be responded by the population mobility management through direct and in indirect policies. Stakeholders (governments-both in the place of origin and destination-, business enterprises, and migrants themselves) should be involved in developping comprehensive solutions to manage the migrants in DKI Jakarta.Keywords: Migration, Temporary migration, Population administration, Slums and squatters.